The electronic structure, elastic properties, dynamical stability and thermoelectric properties of rock-salt and orthorhombic phases of CdS: First-principles calculations. (15th September 2022) - Feng, Xiaoyue; Xue, Feng-ning; Zhao, Peng-bo; Lu, Yong
Abstract: Combined with first-principles calculation and Boltzmann transport theory, we investigated the electronic structure, dynamic stability, mechanical and thermoelectric properties of rock-salt (rs-CdS) and orthorhombic CdS (orth-CdS). Both phases are mechanical and dynamical stable, showing semiconductor characteristics with an indirect band gap of ∼ 0.2 eV and excellent resistance to deformation and external pressure. Due to the strong coupling of optical and acoustic phonon branches, the predicted lattice thermal conductivities of these phases are quite low. The electron transport properties including Seebeck coefficient and power factor of p -type doping are excellent. From 300 K to 800 K, the maximum Z T values are in the range of 0.56 to 0.71 for p -type doping, hinting that the rs-CdS and orth-CdS are superior thermoelectric materials. Highlights: The thermoelectric properties of rs-CdS and orth-CdS were firstly predicted. The electron transport properties of p-type doping are excellent for both phases. The κ l a t values are quite low due to the strong lattice anharmonicity. Both phases are fairly good room-temperature thermoelectric materials.